Effect of different preparation methods on mechanical behaviors of carbon fiber-reinforced PEEK-Titanium hybrid laminates. (May 2020) - Ji, Chunming; Wang, Bing; Hu, Jiqiang; Zhang, Chang'an; Sun, Yuguo
Abstract: This paper aims to investigate the mechanical behaviors of carbon fiber-reinforced PEEK-Titanium hybrid laminates (TiGr) prepared by different surface treatment conditions using silane coupling agent. In order to improve the bonding performance between the titanium sheets and PEEK, the titanium layers were subjected to sandblasting roughening and silanization treatment, the curing process was explored by setting different concentrations of silane coupling agent, curing temperatures and curing times. The optimum parameters of the process were determined by analyzing the mechanical properties of the laminates, which are 10% of SCA concentration, 130 °C of curing temperature and 1 h of curing time, and the corresponding tensile, bending and inter-laminar shearing strengths are 837, 1071 and 75 MPa, respectively. The surface composition, structures and chemical bonding of the modified titanium sheet were analyzed through Scanning Electronic Microscope (SEM), Fourier Transform Infrared Spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS). It was evidenced that the optimal process could produce a relatively complete and uniformed silane film compared to other cases. In addition, the results show that the Si–O–Ti covalent bonds were formed, which demonstrated that the preparation of the laminates through silane coupling agent is reliable. Highlights: Silanization is applied in Ti surface to improve bonding behavior with PEEK. Concentrations, curing temperatures and times are investigated. Optimum parameters of the curing process are obtained. Si–O–Ti covalent bond demonstrates the preparation method is reliable.